PENGARUH BEBERAPA DOSIS ETILEN PADA PEMBUNGAAN TANAMAN NANAS (Ananas comosus L.) VARIETAS QUEEN - Puspitorini, Palupi; Kurniastuti, Tri (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
The study aimed to determine the best dose of ethylene solution in flowering of pineappleplants. The study used a Randomized Block Design (RBD) trial pattern with repeated 4 times.The dose treatment of ethylene concentration, namely: AI = 0.25ml. L A2, A2 = 0.5ml. L A3,A3 = 0.75ml. L¹, A4 = 1 ml. L¹, A5 = 1.25 ml. L¹,A6 = 1.5 ml. L¹, A7 = 1.75 ml. L¹ And 3treatments for each treatment were taken as samples. The results showed that the treatment ofadministration of ethylene 1.5 ml.L¹, is the best treatment for stimulating flowers on pineappleplants.